PUBLIC ADMINISTRATION CHANGES AND THE IMPACT OF THE EU IN LITHUANIA: AGENCIFICATION AND DEPOLITICISATION - NAKROŠIS, VITALIS; BANKAUSKAITĖ-GRIGALIŪNIENĖ, SABINA (Politologija, 2015)
The paper compares the actual patterns of agencification and depoliticisation in Lithuania and explains the extent to which the EU contributed to these changes. Based on the transformational approach and theories of public policy process, our framework for analysis links external factors (including the EU’s influence), internal factors and our dependent variables (changes in public administration and the impact of the EU). Our research employs (descriptive and inferential) statistical analysis of data on the organisational changes of Lithuanian agencies and political participation of their managers. Furthermore, it follows a longitudinal approach to observe ‘net changes’ by mapping agencification and politicisation throughout the period 1990–2012.The paper found that the EU made a significant contribution to the establishment of new agencies driven by the exigencies of EU accession, but its impact on the survival of Europeanised agencies was much smaller after enlargement. Changes in the scope of politicisation can be explained by a combination of evolution in the political conditionality of EU membership and wholesale government changes. The differentiated impact of the EU on public administration changes was observed with the management of the Europeanised agencies becoming increasingly professional over time. Overall, the results of our research confirm the stronger and more enduring impact of specific acquis rules in the EU policy domains compared to the much weaker influence of the EU’s political conditionality. Furthermore, it points to the importance of interactions between domestic actors that realise particular beliefs and pursue certain strategies to understanding institutional and policy changes at domestic level.